Enhancement of phenolic content, antioxidant and cytotoxic activities of Moringa oleifera leaf and seed by suspension culture. Issue 23 (2nd December 2021) - Mustafa, Reham; El-Naggar, E. M. B; Svajdlenka, Emil; Omran, Gamal; ELFiky, Fathy; El-Hawiet, Amr
Abstract: Moringa oleifera Lam. family Moringaceae is well known for a wide range of biological activities and a complex phytochemical composition. The current study investigates tissue culture protocols for Moringa oleifera leaves and seeds. For static culture initiation, Murashige and skooge (MS) as a basal medium with hormonal supply of (0–10 µM) of 2, 4-dicholorophenoxy acetic acid and 6-benzyl aminopurine for Moringa oleifera seeds and leaves was employed. Suspension cultures with the optimum hormonal combination was initiated for both seeds and leaves calli. Liquid chromatography/mass spectroscopy (LC/MS) analysis performed, for the first time, on the methanolic extracts of plant parts and the produced calli revealed varying concentrations of nine major components (six flavonoids and three phenolic acids). Antioxidant and cytotoxic activities, against three cell lines, were evaluated for the obtained methanolic extracts. In general, superior biological activities were identified for the produced calli when compared to plant parts. Graphical Abstract: